1800. Impact of Updated ATS/IDSA CAP Guidelines on Duration of Antibiotics. (15th December 2022) - Petty, Lindsay A; Vaughn, Valerie; Malani, Anurag N; Younas, Mariam; Osterholzer, Danielle; Bernstein, Steven; Ratz, David; McLaughlin, Elizabeth; Czilok, Tawny; Horowitz, Jennifer; Flanders, Scott A; Gandhi, Tejal N
Abstract: Background: In 10/2019, revised ATS/IDSA community-acquired pneumonia (CAP) guidelines removed healthcare-associated pneumonia (HCAP), expanding patients eligible for a 5-day antibiotic course. Using data from 46 hospitals in the Michigan Hospital Medicine Safety Consortium, we quantified the impact of removing HCAP on antibiotic duration for CAP. Methods: From 11/2017 to 1/2022, data were abstracted from medical records of adult non-ICU medical patients admitted with pneumonia. Our primary outcome was percentage of patients who received 5-days of antibiotics out of those who, under the new CAP guidelines would be eligible for 5-days (including patients defined as HCAP prior to the 2019 guideline) [Table 1]. We evaluated using Chi-square, if the effect of the guidelines differed for patients defined as CAP based on the 2007 CAP guideline (pCAP) vs. HCAP. To assess the effect of the new guideline on 5-day therapy, we used segmented logistic regression accounting for hospital level clustering to look at changes at baseline and overtime before and after 10/2019. Results: When applying the 2019 CAP definition to 34, 810 patients admitted with pneumonia over the entire period, 41.2% (N=14, 358) of patients were eligible for 5-day duration. Applying pre-2019 categorization to the entire period, 46.4% of pCAP (N=10, 565/22, 757) and 31.5% of HCAP (N=3793/12, 053) were eligible for 5-day duration. Of those 5-day eligible, 34.4% (N=4, 936) received 5 days (pCAP 35.5% N=3750; HCAP 31.2% N=1186, P< .001). Before 10/2019, 29.5% (N=2, 018) of patients with pCAP who were eligible received 5 days vs 23.6% (N=548) of HCAP (P< .001). Post 10/2019, 46.5% (N=1, 732) of patients with pCAP eligible received 5 days vs 43.5% (N=638) of HCAP (P=0.049). The improvement rate in 5-day therapy decreased after 10/2019, with similar decrements for both pCAP and HCAP [Figure 1 ]. Conclusion: Among patients hospitalized with pneumonia, two thirds received an excess antibiotic duration, with similar proportions for pCAP and HCAP. Prior to the new guidelines, the 5-day treatment rate was improving for HCAP and pCAP. However, the rate of improvement decreased after 10/2019 for both pCAP and HCAP, suggesting the 2019 guidelines did not have an added effect on improving antibiotic duration. Disclosures: Valerie Vaughn, MD, MSc, Thermo Fisher Scientific: Honoraria.